Genetic analysis for seed yield and its related attributes in Yellow Sarson (Brassica rapa var. Yellow Sarson) (Journal of Oilseed Brassica, 2026)
Six generations (P1, P2, F1, F2, BC1, BC2) in each of three crosses were studied to estimate gene effects controlling yield and its related attributes by generation mean analysis and scaling test for ten physiological traits. These were evaluated in a compact family block design (CFBD) with three replications. Besides seed yield per plant, data also recorded for plant height, primary branches per plant, Days to 50% flowering, length of fruiting zone, siliqua per plant, siliqua length, Days of maturity, 1000-seed weight and oil content. The analysis of variance of three cross families revealed significant differences among the progenies (generations) within Family for most of the quantitative traits. Six parameters genetic model revealed the presence of additive (d), dominant (h) and epistasis (i, j, l) for most of the evaluated traits. Significant differences for two or more individual scaling tests (A, B, C, and D) in all three crosses were observed indicating the sight of nonallelic interactions. Further, it was confirmed by joint scaling test. All the crosses showed significant chisquare values for all the evaluated characters except for day to maturity in NDYS 427 x YST-151. Significant chi-square values indicated the presence of epistasis or inadequacy of additive-dominance model. The precise knowledge of nature of gene action for characters evaluated to productivity would aid in the choice of effective breeding methods to accelerate the pace of genetic improvement of seed yield.